Effect of Fertiliser Application on the Growth and Yield of plantago Ovata forsk - Joshi, P.; Tiwari, K. C.; Yadava, B. B. L. (Indian Forester, 1968)
The paper records a Study of the effect of fertiliser applications on freshly prepared terraces in hill soil of pine deforested areas on the growth, development and yield of Plantago ovata Forsk. Results of trials with doses of 112, 280, 504 and 785 kg per hectare of ammonium-sulphate and 125, 249, 374, 498, 622 and 747 kg per hectare of super-phosphate have been presented. Trials suggest that:-(a) The doses of 280 kg ammonium-sulphate and 498 kg super-phosphate result in highest increase in seed yields per bed, viz., 38% and 89% respectively as compared to the control (187 Quintal of F.Y.M. per hectare). (b) The seed yield per hectare on calculated basic with 280 kg per hectare dose of ammonium- sulphate is 896 kg per hectare as compared to control (280 kg/ hectare). Similarly with 498 kg per hectare dose of super-phosphate the yield is 420 kg per hectare as compared to control (309 kg per hectare). (c) Application of ammonium- sulphate in the doses 504 and 785 delayed the maturity by 1 and 2 weeks respectively, while super phosphate doses @ 125, 249 to 498, 622 and 747 kg per hectare hastened the maturity by 1, 2, 3 and 5 weeks respectively. (d) Physical characters of seed remain practically unaltered in the crops from different treatments as compared to control and seed conform to pharmacopocial standards. (e) Plantago ovata crops can be grown in hill. Economically with proper manuring and application of fertilisers.